2018
DOI: 10.7897/2277-4343.09242
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ayurveda Treatment Modalities in the Management of Spasticity in Children With Cerebral Palsy at a Tertiary Care Teaching Hospital of Southern India

Abstract: To assess and compare the effectiveness of Salavana Upanaha Sweda with and without Parisheka on spasticity in children with cerebral palsy. 32 diagnosed cases of Spastic Cerebral Palsy were selected for the study based on the diagnostic criteria and inclusion criteria, later divided into two groups (A and B). The subjects in group A was administered both Parisheka and Upanaha while those in group B with Upanaha only. The duration of study was 90 days, in consecutive 3 sittings of 15 days each with gap of anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…On assessing eligible studies, it was found that most commonly reported efficacy outcome was QOL scale, [13,20,21] Modified Ashworth scale, [12,[14][15][16]19,21,24,[27][28][29][30] manual ability classification system scale, [12,[14][15][16]21,24] gross motor function measure, [13,23,[26][27][28] Development assessment scales for Indian infants, [17] range of motion (ROM). [15,17] Improvement in subjective symptoms such as stiffness and restricted ROM is observed in almost all the studies identified.…”
Section: Results Of Synthesesmentioning
confidence: 99%
See 3 more Smart Citations
“…On assessing eligible studies, it was found that most commonly reported efficacy outcome was QOL scale, [13,20,21] Modified Ashworth scale, [12,[14][15][16]19,21,24,[27][28][29][30] manual ability classification system scale, [12,[14][15][16]21,24] gross motor function measure, [13,23,[26][27][28] Development assessment scales for Indian infants, [17] range of motion (ROM). [15,17] Improvement in subjective symptoms such as stiffness and restricted ROM is observed in almost all the studies identified.…”
Section: Results Of Synthesesmentioning
confidence: 99%
“…Abhyanga is a technique that involves massaging the body with lukewarm medicinal oil. Due to its Snigdh(oily), Mridu(soft), Medhya Churna [12,20,21] Abhaya Ghrita [13] Samvardhana Ghrita [14,28] Ashtangaghrita [15] Baladi Yoga [31] Aarvindaasava [24] 3 1 2 1 1 1…”
Section: Kanzode Et Al 2016mentioning
confidence: 99%
See 2 more Smart Citations